Spatiotemporal assessment of daily temperature extremes in Egypt during 1980–2023 - Mostafa Abd El-Hameed Mohamed; Mohammad Hamdy Darrag; Mohamed Abdelaal Ahmed; Mohamed El-Sayed El-Mahdy (Scientific African, 2025)
Understanding the spatiotemporal fluctuations in climate extreme indices and their contributing factors is essential for addressing climate change. This study provides a comprehensive analysis of the temporal and spatial variations in eight extreme climate indicators, derived from daily maximum and minimum temperatures recorded between 1980 and 2023. Data were collected from 30 meteorological stations across Egypt. Linear trend analysis revealed an increasing trend in SU25, WSDI, TX90P, and TN90P, indicating a rise in the frequency and persistence of warm conditions. In contrast, DTR, CSDI, TN10P, and TX10P exhibited a decreasing trend, reflecting a decline in cold extremes. Over the past three decades, significant shifts in maximum and minimum temperatures have been observed. The maximum temperature indices, particularly TX90P, TN90P, TX10P, and TN10P, displayed distinct temporal patterns, with TX10P and TN10P showing a clear downward trend. These findings strongly confirm an overall warming trend across the study area. The upward trends in extreme warm conditions suggest that heatwaves and prolonged high-temperature events have become more frequent. This pattern aligns with global climate change trends, reinforcing the impact of rising global temperatures and increasing climate variability in the region.